ASSESSING NURSING TECHNICIANS’ KNOWLEDGE, ATTITUDES AND PRACTICES RELATED TO SAFE PATIENT HANDLING AND MOBILITY: A MIXED METHODS STUDY - Taeebah Dakhel Khudhayr Alanezi1, Naimah Shahadah Ali Alanazi2, Norah Ayad Surur Almutairi3, Mohammed Muharib Kh Aldahmshi4, Eman Sultan Haylan Alanazi5, Nashmiah Reja F Al- Dhefiri6 (Chelonian Research Foundation, 2022)
Safe patient handling is vital to avoid musculoskeletal injuries among healthcare workers. This mixed methods study assessed knowledge, attitudes, and practices regarding safe lifting principles and mobility assistance among 100 nursing technicians across three hospitals in Saudi Arabia. Surveys revealed moderate knowledge but suboptimal attitudes and adherence regarding using mechanical aids versus manual lifting. Technicians cited lack of devices, time pressure, and cultural norms around physical assistance as barriers. Integrated results inform targeted interventions through training, technology provisions, protocol revisions, and culture change to enhance safe handling compliance. Findings provide insights to strengthen nursing assistant lifting practices to reduce preventable injuries and enhance a culture of safety. Keywords: safe patient handling; nursing technicians; knowledge, attitudes, practices; mixed methods